2013
DOI: 10.4161/auto.22397
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is differentially induced in prostate cancer LNCaP, DU145 and PC-3 cells via distinct splicing profiles of ATG5

Abstract: Autophagic responses to chemotherapeutic agents may vary greatly among different prostate cancer cells and have not been well characterized. In this study, we showed that valproic acid (VPA) induced conversion of LC3-I to LC3-II and formation of LC3 puncta, the typical markers of autophagy, in LNCaP and PC-3 cells. However, these markers were undetectable in DU145 cells upon autophagic stimulation, indicating a defect of autophagy in this cell line. Among several critical autophagy-related proteins, ATG5 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 50 publications
(61 reference statements)
9
90
2
1
Order By: Relevance
“…2A). This observation was not unexpected as the lack of one or two exons in ATG5 interferes with the formation of LC3-II in DU145 cells (12). Consistently, EGFP-LC3 puncta was not be observed in Tet-treated DU145 cells (Fig.…”
Section: Tetrandrine Fails To Induce Lc3 Conversion In Du145 Cellssupporting
confidence: 61%
See 4 more Smart Citations
“…2A). This observation was not unexpected as the lack of one or two exons in ATG5 interferes with the formation of LC3-II in DU145 cells (12). Consistently, EGFP-LC3 puncta was not be observed in Tet-treated DU145 cells (Fig.…”
Section: Tetrandrine Fails To Induce Lc3 Conversion In Du145 Cellssupporting
confidence: 61%
“…Therefore, evaluation of autophagy using LC3-based It has been reported that serum starvation, CQ treatment and rapamycin treatment all failed to induce LC3-I to LC3-II conversion in DU145 cells (12). Due to the lack of functional products of ATG5, the LC3-I to LC3-II conversion is blocked (12). Therefore, the EGFP-LC3 marked autophagosomes could not be observed in DU145 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations